Application Employee Competencies for Geographic Information System (GIS) Website Digitalization - Amaliyah Amaliyah; Rizky Amalia Sinulingga; Erindah Dimisqiyani; Citra Widhi Apsari (AIBPM Publisher, 2024)
The rapid advancement of technology has become integral to all aspects of modern life. This research examines the relationship between employee competency and the use of a digitalized GIS website for managing customer data, focusing on employees at PDAM Surabaya City. The study involved 100 participants and employed a quantitative descriptive approach, utilizing data collection techniques such as observation, interviews, and surveys through questionnaires. Findings reveal that while employees generally believe their education and technological skills are well-suited to their job roles and support their performance, there are notable issues with the GIS website's reliability and error management. Statistical analysis confirms that employee competencies significantly impact the effective use of the GIS website, underscoring the importance of skill development in optimizing digital tool utilization and enhancing organizational efficiency. The research implies that improving employee competencies and addressing technical issues with the GIS website are essential for enhancing its utilization and overall organizational performance.Abdillah, M. Z., Nawangnugraeni, D. A., Yuniarto, A. H. P. (2021). Geographic information system (GIS) for mapping greenpark using leaflet JS. Jurnal Teknik Informatika Kaputama, 5(2), 259-266. Aelani, K. (2021). Pengujian Kualitas Website menggunakan Metode McCall Software Quality (Studi Kasus smkn4bdg. sch. id) [Website Quality Testing using the McCall Software Quality Method (Case Study smkn4bdg. sch. id)]. Journal of Information Technology, 3(1), 25-32. https://doi.org/10.47292/joint.v3i1.43Ahyar, J., Zainuddin, Z., Maulana, I., Kurniawan, R. (2021). Optimalisasi digitalisasi arsip pada Kantor Mahkamah Syar’iyah [Optimization of archive digitization at the Sharia Court Office]. Asia-Pacific Journal of Public Policy, 7(1), 49-67. https://doi.org/10.52137/apjpp.v7i1.62Alam, N., Tajang, A. R., Taufik, A. (2022). Pengaruh budaya organisasi dan kompetensi terhadap kinerja pegawai Kantor Kelurahan Daya Kota Makassar [The influence of organizational culture and competence on the performance of employees at the Daya Subdistrict Office, Makassar City]. Jurnal Online Manajemen ELPEI, 2(1), 286-300.https://doi.org/10.58191/jomel.v2i1.65Anjani, A. (2019). Pengaruh kompetensi dan motivasi kerja terhadap kinerja karyawan [The influence of competence and work motivation on employee performance]. Jurnal Inspirasi Bisnis dan Manajemen, 3(1), 3-5 https://doi.org/10.33603/jibm.v3i1.2191Basyit, A., Sutikno, B., Dwiharto, J. (2020). Pengaruh tingkat pendidikan dan pengalaman kerja terhadap kinerja karyawan [The influence of education level and work experience on employee performance]. Jurnal Ekonomi Manajemen, 5(1), 12-20. http://dx.doi.org/10.47335/ema.v5i1.44Budiman, A., Sunariyo, S., Jupriyadi, J. (2021). Sistem informasi monitoring dan pemeliharaan penggunaan SCADA (Supervisory Control and Data Acquisition) [Information system for monitoring and maintenance of SCADA (Supervisory Control and Data Acquisition) usage]. Jurnal Tekno Kompak, 15(2), 168-179.https://doi.org/10.33365/jtk.v15i2.1159Cakranegara, P., Fetesond, M. (2022). Pengaruh literasi keuangan, kemampuan akademis dan pengalaman berkerja terhadap prilaku keuangan mahasiswa [The influence of financial literacy, academic ability and work experience on students' financial behavior]. Jurnal Ekonomi Dan Bisnis, 9(1), 259–274. https://doi.org/10.34308/eqien.v9i1.333Chinnapong, P., Aujirapongpan, S., Koompai, S., Dowpiset, K., Jiraphanumes, K. (2021). The effect of information technology and dynamic capabilities on human resources competencies and innovative performance. ABAC Journal, 41(4), 198-223.https://doi.org/10.14456/abacj.2021.10Eliana, E. (2020). Pengaruh pendidikan dan pelatihan (DIKLAT) terhadap kinerja pegawai pada BPSDM Aceh [The influence of education and training (DIKLAT) on employee performance at BPSDM Aceh]. ZONAsi: Jurnal Sistem Informasi, 2(2), 84-95.https://doi.org/10.31849/zn.v2i2.4864Elizar, E., Tanjung, H. (2018). Pengaruh pelatihan, kompetensi, lingkungan kerja terhadap kinerja pegawai [The influence of training, competence, work environment on employee performance]. Maneggio: Jurnal Ilmiah Magister Manajemen, 1(1), 46-58. https://doi.org/10.30596/maneggio.v1i1.2239Fatimatuzahra, D. T., Somantri, S. (2023). Perancangan Web Geographic Information System (WebGIS) kehutanan pada wilayah Sukabumi [Design of Web Geographic Information System (WebGIS) for forestry in Sukabumi area]. Jurnal Tekno Kompak, 17(1), 184-195. https://doi.org/10.33365/jtk.v17i1.2433Fauzi, A. A., Kom, S., Kom, M., Budi Harto, S. E., Mm, P. I. A., Mulyanto, M. E., ... Rindi Wulandari, S. (2023). Pemanfaatan Teknologi Informasi di Berbagai Sektor Pada Masa Society 5.0. [Utilization of Information Technology in Various Sectors in the Society 5.0 Era]. PT Sonpedia Publishing Indonesia.Fuller, M., Heijne-Penninga, M., Kamans, E., van Vuuren, M., de Jong, M., Wolfensberger, M. (2018). Identifying competence characteristics for excellent communication professionals: A work field perspective. Journal of communication management, 22(2), 233-252. https://doi.org/10.1108/JCOM-07-2016-0051Hardiyanti, U., Melita, D. (2018). Sistem penyimpanan arsip pada Kantor Imigrasi Kelas 1 Palembang [Archive storage system at the Class 1 Palembang Immigration Office]. Prosiding Semhavok, 1(1), 26-35. Hasanah, Y. M., Permana, P. S. (2020, November). Implementation management of character education. In International Conference Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Imam Bonjol Padang (pp. 82-88). Redwhite Press. Hidayati, A., Oktariza, E., Rosmaningsih, F., Lathifah, S. A. (2017). Analisa kualitas perangkat lunak sistem informasi akademik menggunakan McCall [Analysis of academic information system software quality using McCall]. Jurnal Multinetics, 3(1), 47-51. Hutahaean, W. S. (2021). Dasar Manajemen [Management Basics]. Ahlimedia Book.Ibrahim, F. E., Djuhartono, T., Sodik, N. (2021). Pengaruh kerjasama tim terhadap kinerja karyawan di PT LION Superindo [The influence of teamwork on employee performance at PT LION Superindo]. Jurnal Arastirma, 1(2), 316-325. Jailani, M. S. (2023). Teknik pengumpulan data dan instrumen penelitian ilmiah pendidikan pada pendekatan kualitatif dan kuantitatif [Data collection techniques and instruments for scientific educational research using qualitative and quantitative approaches]. IHSAN: Jurnal Pendidikan Islam, 1(2), 1-9. https://doi.org/10.61104/ihsan.v1i2.57Kapur, R. (2022). Leadership management and development in organizations. International Journal of Information, Business and Management, 14(2), 47-57. Kim, M., Beehr, T. A. (2018). Organization-based self-esteem and meaningful work mediate effects of empowering leadership on employee behaviors and well-being. Journal of Leadership Organizational Studies, 25(4), 385-398. https://doi.org/10.1177/1548051818762337Leggett, E. R. (2020). Digitization and Digital Archiving: A Practical Guide for Librarians (Vol. 71). Rowman Littlefield Publishers. Mahendra, H. (2023). Perancangan dan implementasi Sistem Informasi Geografis (SIG) dengan teknologi Global Positioning System (GPS) untuk pemetaan dan navigasi [Design and implementation of Geographic Information Systems (GIS) with Global Positioning System (GPS) technology for mapping and navigation]. Review Jurnal SIG, 3(5), 1-16.Meidita, A. (2019). Pengaruh pelatihan dan kompetensi terhadap kepuasan kerja melalui motivasi kerja [The influence of training and competence on job satisfaction through work motivation]. Maneggio: Jurnal Ilmiah Magister Manajemen, 2(2), 226-237.https://doi.org/10.30596/maneggio.v2i2.3772Mualim, A., Srisulistiowati, D. B., Rejeki, S., Anggiani, S. (2023). Developing human resource management in increasing sustainable competitive advantage in SMAN 4 Bekasi Student. Jurnal Ekonomi, Manajemen, dan Akuntansi, 9(6), 2960-2970. https://doi.org/10.35870/jemsi.v9i6.1873Nugraha, F. A., Muryono, S., Utami, W. (2021). Membangun sistem informasi penggunaan tanah berbasis bidang tanah di Desa Blimbing Kecamatan Gatak Kabupaten Sukoharjo [Building a land use information system based on land areas in Blimbing Village, Gatak District, Sukoharjo Regency]. Jurnal Tunas Agraria, 4(1), 146-157.https://doi.org/10.31292/jta.v4i1.140Nurhayati, R., Suprapti, S. (2019). Kinerja pegawai dilihat dari kemampuan kerja, disiplin kerja dan team work pada pegawai Dinas Kesehatan Kabupaten Pemalang [Employee performance is seen from work ability, work discipline and team work of the Pemalang Regency Health Service employees]. Serat Acitya, 8(1), 41. http://dx.doi.org/10.56444/sa.v8i1.1036Odja, M., Hamzah, N., Arifin, Z. (2020). Pengaruh kompetensi SDM, teknologi informasi dan komunikasi organisasi terhadap kinerja pegawai Dinas Lingkungan Hidup Kota Makassar [The influence of HR competency, information technology and organizational communication on the performance of employees of the Makassar City Environmental Service]. Journal of Management Science, 1(1), 105-119. Oktafina, A., Jannah, F. A., Rizky, M. F., Ferly, M. V., Tangtobing, Y. D., Natasia, S. R. (2021). Website usability evaluation using heuristic evaluation method (study case: XYZ City Public Works Office). Antivirus: Jurnal Ilmiah Teknik Informatika, 15(2), 134-146. https://doi.org/10.35457/antivirus.v15i2.1553Pangestu, A., Siregar, M. Y., Lailikhatmisafitri, I. (2020). Pengaruh pengembangan sumber daya manusia dan human relations (hubungan antar manusia) terhadap kinerja karyawan Badan Pengawas Obat dan Makanan Kota Medan [The influence of human resource development and human relations on the performance of employees of the Medan City Food and Drug Supervisory Agency]. Jurnal Ilmiah Manajemen dan Bisnis, 1(1), 1-10. https://doi.org/10.31289/jimbi.v1i1.362Pinatik, S. (2021). The effect of auditor's emotional intelligence, competence, and independence on audit quality. International Journal of Applied Business and International Management, 6(2), 55-67.https://doi.org/10.32535/ijabim.v6i2Reddy, G. O. (2018). Geographic information system: Principles and applications. Geospatial Technologies in Land Resources Mapping, Monitoring and Management, 45-62. https://doi.org/10.1007/978-3-319-78711-4_3Rios, J. A., Ling, G., Pugh, R., Becker, D., Bacall, A. (2020). Identifying critical 21st-century skills for workplace success: A content analysis of job advertisements. Educational Researcher, 49(2), 80-89. https://doi.org/10.3102/0013189X19890600Ritter, T., Pedersen, C. L. (2020). Digitization capability and the digitalization of business models in business-to-business firms: Past, present, and future. Industrial Marketing Management, 86, 180-190. https://doi.org/10.1016/j.indmarman.2019.11.019Robbins, S. P., Judge, T. A. (2019). Perilaku Organisasi [Organizational Behavior] (16th ed.). Salemba Empat.Rumawas, W. (2018). The role of human capital to the improvement of employee performance in fisheries companies in North Sulawesi Province. International Journal of Applied Business and International Management, 3(2), 71-78.https://doi.org/10.32535/ijabim.v3i2.160Sari, K. A. D. P., Suryandari, N. N. A., Putra, G. B. B. (2021). Pengaruh pemanfaatan teknologi, partisipasi pemakai, kemampuan teknik pemakai, pengalaman kerja dan jabatan terhadap efektivitas sistem informasi akuntansi [The influence of technology utilization, user participation, user technical skills, work experience and position on the effectiveness of accounting information systems]. Kumpulan Hasil Riset Mahasiswa Akuntansi, 3(1), 104-109.Sitompul, J., Sihombing, S. Y., Pesik, L. N., Riyanto, I. (2019) Sistem Penggunaan Aplikasi Aset Management Berbasis GIS Web di PT Multitech Yasa Guna [Web-based GIS Asset Management Application Usage System at PT Multitech Yasa Guna]. Jurnal Fakultas Teknik Universitas Budi Luhur, 3(2), 73-79Utama, S. T. (2020). Pengaruh disiplin kerja dan pengembangan karir sumber daya manusia terhadap kinerja dan prestasi perusahaan [The influence of work discipline and human resource career development on company performance and achievements]. Jurnal Manajemen Pendidikan dan Ilmu Sosial, 2(1), 281-287. https://doi.org/10.38035/jmpis.v2i1.449Wahyuningsih, S. (2019). Pengaruh pelatihan dalam meningkatkan produktivitas kerja karyawan [The influence of training in increasing employee work productivity]. Jurnal Warta Dharmawangsa, 13(2), 11-15.https://doi.org/10.46576/wdw.v0i60.413Wesly, J., Kristiana, V., Bong, T., Saputra, N. (2021). Pengaruh digital leadership, total quality management, dan knowledge management terhadap sustainability management pada perusahaan di DKI Jakarta [The influence of digital leadership, total quality management, and knowledge management on sustainability management in companies in DKI Jakarta]. Studi Ilmu Manajemen dan Organisasi, 2(2), 97-124. https://doi.org/10.35912/simo.v2i2.543Wulandari, I. W., Hwihanus, H. (2023). Peran sistem informasi akutansi dalam pengaplikasian enkripsi terhadap peningkatan keamanan perusahaan [The role of accounting information systems in the application of encryption to improve corporate security]. Jurnal Kajian dan Penalaran Ilmu Manajemen, 1(1), 11-25.https://doi.org/10.59031/jkpim.v1i1.46Zuama, M., Sudiarditha, I. K. R., Wolor, C. W. (2023). Leadership determination and training effectiveness on employee performance through work motivation mediation. International Journal of Applied Business and International Management, 8(2), 113-127. https://doi.org/10.32535/ijabim.v8i1.2132